Securing the Future of Higher Education in England - Esson, J; Ertl, H (2013)
This article reviews the IPPR commissioned report 'Securing the Future of Higher Education in England'. It is argued that the report identifies key shortcomings in contemporary higher education policy, and develops some important recommendations for shaping the sector in the future. However, several of the proposed recommendations would create new divisions in the sector and reinforce existing ones. Moreover, the report maintains and reproduces the ideological status quo of contemporary higher education policy, which can broadly be described as the organisation and provision of higher education along 'quasi-market' lines. Crucially, although the report advocates reform based on social justice, in the contemporary context of fiscal retrenchment, the majority of recommendations are underpinned by, arguably necessary, economic rationales. © The Political Quarterly Publishing Co. Ltd. 2013.